The Effect of Hidden Time Loss Measures Components from Aspect of Assembly Features Perspective in Automotive Industry - Rasib A. H., Abdul; Rafaai Z.F, Mohamad; ., . (International Journal of Engineering and Technology, 2018)
Hidden Time Loss (HTL) usually effect on productivity during the production processes. Normally, top performance measurement tool is used in the production assembly line such as Overall Equipment Efficiency (OEE). In order to provide HTL, equipment performance as one of the measure components of OEE is used in order to provide HTL. In scope of assembly process especially the manual and the semi-auto in the assembly process, OEE does not suitable in measuring those operation performance. There should be the value of HTL have happened during the manual and semi-auto processes that become serious while related to aspect assembly features such as left and right components, product type/variety, model type/variety, and rear & front component in one production line. In this regards, the objective of this study is to present the Hidden Time Loss Measures (HTLM) components and itsâ€™ effect to HTL based on the aspect of assembly features. The structure of HTLM components are designed through a detail literature review on production assembly line and its performance measures. The case study at five automotive manufacturing assembly companies in Malaysia is used to validate the HTLM components structure. The outcomes show that there is significant effect of HTLM components on production productive time in the aspects of assembly features.Â Â